Reverse and Reserve : a Cardiff Grammar account on reversibility in equational clauses in modern standard Arabic - Hanaa Samaha; Yap, Teng Teng; Kumaran Rajandran (Penerbit Universiti Kebangsaan Malaysia, 2021)
The sequence of clause elements not only determines the syntactic relations of categories but also recognizes the semantic and pragmatic roles associated with them. Therefore, this paper aims to examine reversibility in verbless Equational Clauses (ECls) by investigating the syntactic, experiential (Transitivity), and textual (thematic and informational) features of the reversed elements in Modern Standard Arabic (MSA) within the Cardiff Grammar model (CG). The data consists of 138 ECls collected from twelve articles in seven daily newspapers, out of which thirty-one ECls have been identified as reversed. The findings have revealed that Subject and Complement can be optionally reversed in ECls to achieve discourse purposes. In this case, when optional reversibility represents the Unmarked Participant Role Theme, the reversed elements retain none of their syntactic, experiential, thematic, and informational meanings. But when optional reversibility reflects the Marked Participant Role Theme, the reversed elements retain their syntactic and experiential functions but not necessarily their thematic and informational meanings. On the other hand, obligatory reversibility has been argued to stem from the syntactic constraints concerning the violation of the definiteness norm and the pragmatic factors. Finally, the paper concludes that the association of the ‘Theme’ concept with what comes early in the clause should not be taken as a universally unified concept applied to all languages. The findings imply that in designing syllabi for language learning and teaching, learners should be made aware of the significant interplay of linguistic and extra-linguistic factors that cause the inversion of the clause elements. This would probably help them reflect on understanding the sentences they receive and produce in different contexts.